Incumbernt Versus Big Coalition: Incumbent's Failure as Regional Head Candidate in Wonosobo [Petahana Versus Koalisi Gemuk: Kegagalan Petahana Sebagai Calon Kepala Daerah dalam Pilkada di Wonosobo] - Romli, Lili; Irawan, Candra (Sekretariat Jenderal DPR RI, 2024)
This research focuses on the study of incumbents in Wonosobo Regency. The incumbent is seen as a candidate who has a high chance of running again as a candidate. Other studies have also looked at many incumbents running as single candidates. This research uses interview methods and literature studies using the oligarchy concept. the results of this study are that in the case of Wonosobo Regency,the incumbent failed to run as a candidate for regional head. With this failure, it shows that incumbents who have been seen as actors who can control political parties to nominate again, are the opposite of the case in Wonosobo where political parties can be independent. There are several factors that cause it. First, related to the parties' dissatisfaction with the incumbent leadership. Second, the leadershipstyle of the incumbent regent is distant from political parties. Third, existing political parties do not provide support for the incumbent's re-nomination. Fourth, the formation of a large coalition built by PDIP. This research uses a qualitative approach, with data collection methods of in-depth interviews and literature study.AbstrakPada beberapa kajian, incumbent dilihat sebagai calon yang memiliki peluang besar untuk maju kembali sebagaai calon. Kajian yang lain juga melihat bahwa banyak incumbent maju sebagai calon tunggal. Dalam kasus di Kabupaten Wonosobo yang terjadi sebaliknya,incumbent gagal maju sebagi calon kepala daerah. Dengan kegagalan tersebut menunjukkan bahwa incumbent yang selama ini dilihat sebagi aktor yang bisa mengendalikan partai-partai politik untuk mencalonkan kembali, untuk kasus di Wonosobo sebaliknya di mana partaipolitik bisa bersifat independent. Ada beberapa faktor yang menjadi penyebab. Pertama, terkait dengan ketidakpuasan partai-partai terhadap kepemimpinan petahana. Kedua, gaya kepemimpinan bupati petahana yang berjarak dengan partai politik. Ketiga, partaipartai politik yang ada tidak memberikan dukungan untuk pencalonan kembali petahana. Keempat, terbentuknya koalisi besar yang dibangun oleh PDIP. Penelitian ini menggunakan pendekatan kualitatif, dengan metode pengumpulan data berupa wawancara mendalam dan studi pustaka.